Gender Inequalities in the Dental Workforce: Global Perspectives. (December 2019) - Tiwari, T.; Randall, C.L.; Cohen, L.; Holtzmann, J.; Webster-Cyriaque, J.; Ajiboye, S.; Schou, L.; Wandera, M.; Ikeda, K.; Fidela de Lima Navarro, M.; Feres, M.; Abdellatif, H.; et al.
The aim of this review is to investigate the growth of diversity and inclusion in global academic dental research with a focus on gender equality. A diverse range of research methodologies were used to conduct this review, including an extensive review of the literature, engagement of key informants in dental academic leadership positions around the world, and review of current data from a variety of national and international organizations. Results provide evidence of gender inequalities that currently persist in dental academics and research. Although the gender gap among graduating dental students in North America and the two most populous countries in Europe (the United Kingdom and France) has been narrowed, women make up 30% to 40% of registered dentists in countries throughout Europe, Oceania, Asia, and Africa. In academic dentistry around the globe, greater gender inequality was found to correlate with higher ranking academic and leadership positions in the United States, United Kingdom, several countries in European Union, Japan, and Saudi Arabia. Further disparities are noted in the dental research sector, where women make up 33% of dental researchers in the European Union, 35% in North America, 55% in Brazil, and 25% in Japan. Family and societal pressures, limited access to research funding, and lack of mentoring and leadership training opportunities are reported as also contributing to gender inequalities. To continue advancing gender equality in dental academia and research, efforts should be geared toward the collection and public dissemination of data on gender-specific distributions. Such evidence-driven information will guide the selection of future strategies and best practices for promoting gender equity in the dental workforce, which provides a major pipeline of researchers and scholars for the dental profession.